Caracterización de las mipymes sostenibles del sector turístico del Estado de Baja California, México (2019)
The growing concern of the state of Baja California towards the sustainability of its businesses is derived from its geographical proximity with United States of America and the requirements demanded by local and foreign tourism, which each time show great interest in the social, economic, and environmental aspects, and which forces owners of micro, small, and medium-sized enterprises (msmes) to offer their products or services with such requirements. The tourism sector is one of the most demanded at a national level, by consumers of products and services that are concerned about sustainable development, which create the need to study sustainable tourism as a competitiveness strategy. The tourism industry in Baja California has been an important source of income in the last decade, which allows an international projection due to its geographical nature and cultural exchange. Literature shows that in Colombia, in Bogota and Manizales, ecological tourism parks have been implemented as a sustainable development alternative, thus increasing their Gross Domestic Product (gdp) as economic indicator and the creation of new jobs as social indicator. With respect to the state of Baja California, sustainable tourism and its degree of management in msmes is an unexplored topic. The objective of this study is to identify the degree of sustainable management of msmes in Baja California that belong to the tourism sector. The methodology is descriptive and correlational. To date, msmes from the municipalities of Tijuana and Mexicali have been studied, and the survey was used as a tool to collect data. It was observed that there are significant differences in the type of tourism the enterprises receive, the effect of the migratory situation of the organizations, the advertising used, and the government support, among others.